2018
DOI: 10.1002/anie.201803201
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Vise Approach to Create Metal‐Binding Sites in MOFs and Detection of Biomarkers

Abstract: We report a new approach to create metal-binding site in a series of metal-organic frameworks (MOFs), where tetratopic carboxylate linker, 4',4'',4''',4''''-methanetetrayltetrabiphenyl-4-carboxylic acid, is partially replaced by a tritopic carboxylate linker, tris(4-carboxybiphenyl)amine, in combination with monotopic linkers, formic acid, trifluoroacetic acid, benzoic acid, isonicotinic acid, 4-chlorobenzoic acid, and 4-nitrobenzoic acid, respectively. The distance between these paired-up linkers can be preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 46 publications
(8 reference statements)
1
34
0
2
Order By: Relevance
“…etal-organic frameworks (MOFs) are emerging porous materials that have shown promise in cancer therapy 1,2 , catalysis [3][4][5] , chemical sensing 6,7 , and energy-storage applications [8][9][10][11] , including as electrodes, [12][13][14][15][16][17][18][19][20] separators 21,22 , and electrolytes 23 , due to their high surface area 24 , abundant ordered pores 25 , and tailored pore environment 26 . Zirconium-based MOFs (Zr-MOFs) are promising framework materials for practical applications because of their higher thermal and chemical stability compared with other MOFs 27,28 .…”
mentioning
confidence: 99%
“…etal-organic frameworks (MOFs) are emerging porous materials that have shown promise in cancer therapy 1,2 , catalysis [3][4][5] , chemical sensing 6,7 , and energy-storage applications [8][9][10][11] , including as electrodes, [12][13][14][15][16][17][18][19][20] separators 21,22 , and electrolytes 23 , due to their high surface area 24 , abundant ordered pores 25 , and tailored pore environment 26 . Zirconium-based MOFs (Zr-MOFs) are promising framework materials for practical applications because of their higher thermal and chemical stability compared with other MOFs 27,28 .…”
mentioning
confidence: 99%
“…Deng and co‐workers in their recent report have introduced a novel metalation strategy inside the MOFs by staging the metal ions between two rigid ligands in a vise like manner . They established the molecular vise approach with MOF PCN‐521, fabricated of tetratopic organic ligands (4′,4′′,4′′′,4′′′′‐methanetetrayltetrabiphenyl‐4‐carboxylic acid, MTBC).…”
Section: “Turn On” Sensing Based On Mofsmentioning
confidence: 99%
“…[52] Deng and co-workersi nt heir recent report have introduced an ovel metalation strategy inside the MOFs by staging the metal ions between two rigid ligands in av ise like manner. [53] They established the molecular vise approach withM OF PCN-521, fabricated of tetratopic organic ligands (4',4'',4''',4''''-methanetetrayltetrabiphenyl-4-carboxylic acid, MTBC). The tetratopic ligand was partly replaced by two tritopic ligand,t ris(4-carboxybiphenyl) amine (TBPA) and a single monotopic ligand resulting the formation of MV-MOF (MVPCN-521-R).…”
Section: Sensing Of Bio-markersa Nd Biologically Active Compoundsmentioning
confidence: 99%
“…This is common to framework materials made of reversible linkage chemistry, where ligand substitution reactions or dynamic covalent chemistry can take place, as exemplified by replacing tetratopic carboxylate linker in PCN-521 by a tritopic linker, leaving an unconnected site. [23] Other than permanent disconnection, dynamic dissociation of building units can take place, facilitated by the temporary bonding of foreign ligands. It was revealed that the Zn 2+ ions in MOF-5 bind solvent molecules, thereby increasing their coordination number and dynamically dissociating from the framework even at low temperatures.…”
Section: Defective Adaptation To Guest Speciesmentioning
confidence: 99%